Developing Farmers' Business in Utilizing Coffee Skin Waste In Turekisa Village Through Biochar Production, Implementation, And Marketing for Sustainable Value Added Increase (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
One of the specialty coffees produced in Indonesia is Flores Bajawa Arabica coffee, known as Flores coffee. Coffee, as the main commodity produced by farmers in Turekisa Village, has a low production level compared to other regions. The purpose of this activity is to implement GAP in plantation cultivation and technology for processing coffee skin agricultural waste into biochar as an effective and efficient program development activity in reducing poverty, providing direct benefits to farmer group partners, and opening up job opportunities for small and medium groups. This community service activity uses the Participatory Learning and Action (PLA) method, consisting of several stages of activities. namely the preparation stage of activities and coordination with partners, literature studies for the preparation of socialization materials, training and dissemination, the implementation stage of PKM activities (production, management, science and technology), the method of approach and application of technology and innovation (Analysis and design, socialization and training as well as the implementation and supervision stage). This program has succeeded in increasing the knowledge and technical skills of farmers in implementing organic coffee cultivation SOPs through the application of GAP and environmentally friendly Biochart processing by utilizing agricultural waste through the pyrolysis process. This program has also succeeded in developing the marketing capacity of the More Masi Group by equipping farmers with branding skills, attractive packaging design, and digital marketing strategies to expand market reach.